2008
DOI: 10.1073/pnas.0711733105
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneities in granular dynamics

Abstract: The absence of Brownian motion in granular media is a source of much complexity, including the prevalence of heterogeneity, whether static or dynamic, within a given system. Such strong heterogeneities can exist as a function of depth in a box of grains; this is the system we study here. First, we present results from three-dimensional, cooperative and stochastic Monte Carlo shaking simulations of spheres on heterogeneous density fluctuations. Next, we juxtapose these with results obtained from a theoretical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 27 publications
5
31
0
Order By: Relevance
“…Prior work indicated that the particles rearrange in cooperative groups [23], similar to what is seen in supercooled liquids [3,33,45,46,47,48,49,50,51] and granular materials [52,53]. A starting point to look for cooperativity is to ask where the mobile particles are located [23,46,49]; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Prior work indicated that the particles rearrange in cooperative groups [23], similar to what is seen in supercooled liquids [3,33,45,46,47,48,49,50,51] and granular materials [52,53]. A starting point to look for cooperativity is to ask where the mobile particles are located [23,46,49]; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…First, computer simulations [7] of shaken sphere assemblies verified that the time-averaged value of density about which temporal fluctuations occur, is an increasing function of depth ( Fig. 2) and additionally predicted that the range of density fluctuations is greatest in the middle of the box [13,14]. Initially surprising, this is easily explained as follows: the top is barely fluidized, with few fluctuations about an overall low density while the jammed region near the bottom also has only very slow density fluctuations.…”
Section: Spatiotemporal Heterogeneities: a Model Granular Column Nearmentioning
confidence: 81%
“…More specifically, they verified that the time-averaged value of density, about which temporal fluctuations occur, is an increasing function of depth. 13 One of the most surprising features of those results, at least at first glance, is that the range of density fluctuations is greatest near the middle of the column, as seen in figure 3. However, that feature can be simply explained.…”
Section: Fluctuations and Correlationsmentioning
confidence: 88%
“…That theoretical tool monitors the propagation of order in a system at minimal perturbation; here, the dynamics are reflected in the behavior of the ordering length-that is, the length over which the column is ordered-at zero vibrational intensity (see figure 5). 13 A complete picture of spatiotemporal heterogeneity emerges from particle behavior in different regions. At the top of the column, the dynamics are ballistic: Grains move fast and freely in response to vibrational excitations.…”
Section: Tops Middles and Bottomsmentioning
confidence: 99%
See 1 more Smart Citation